2017
DOI: 10.5505/ptd.2017.15579
|View full text |Cite
|
Sign up to set email alerts
|

Determining implementation status of pediatric nurses’ roles and functions

Abstract: ÖzetAmaç:Bu araştirma pediatri hemşirelerinin rol ve fonksiyonlarini uygulama durumlarinin belirlenmesi amaciyla tanimlayici olarak yürütülmüştür. Gereç veYöntem: Araştirma 118 pediatri hemşiresi ile yürütülmüştür. Araştirma verileri "Pediatri Hemşirelerine Yönelik Tanimlayici Bilgiler Formu" ve "Pediatri Hemşirelerinin Rolleri ve Fonksiyonlari Ölçeği" ile toplanmiştir. Elde edilen veriler tanimlayici testler, tek yönlü varyans analizi ve independent samples t test uygulanarak değerlendirilmiştir. Bulgular:Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…In their study, Çetinkaya et al, found that the paediatric nurses had higher levels of fulfilling their roles and functions, which is compatible with the present study. 26 When examining the Paediatric Nurses' Roles and Functions Scale mean scores, it was seen that there was a high score distribution in all subscales. It was seen that the paediatric nurses fulfilled each role (caregiving and health protecting, training and researching, defending and decision making, relaxing, rehabilitating, counselling, managing and coordinating, and communicating and collaborating) with the same approach.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Çetinkaya et al, found that the paediatric nurses had higher levels of fulfilling their roles and functions, which is compatible with the present study. 26 When examining the Paediatric Nurses' Roles and Functions Scale mean scores, it was seen that there was a high score distribution in all subscales. It was seen that the paediatric nurses fulfilled each role (caregiving and health protecting, training and researching, defending and decision making, relaxing, rehabilitating, counselling, managing and coordinating, and communicating and collaborating) with the same approach.…”
Section: Discussionmentioning
confidence: 99%